ANALISIS PEMECAHAN MASALAH MATEMATIKA DAN KOMUNIKASI MATEMATIK MAHASISWA DENGAN PENERAPAN MODEL PROJECT-BASED LEARNING (PJBL) TERINTEGRASI ETNOMATEMATIKA - Hersiyati Palayukan; Al Ikhlas; Rendi Hadian A. Tamagola; Gusnidar; Loria Wahyuni; Joni Wilson Sitopu (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study aims to analyze students' mathematical problem-solving skills and mathematical communication through the implementation of the Project-Based Learning (PjBL) model integrated with ethnomathematics. This model is designed to enhance students' ability to deeply understand mathematical concepts by utilizing local cultural contexts as a medium for learning. The research employed a quasi-experimental method with a non-equivalent control group design. The study subjects comprised mathematics education students from a university. Data were collected through mathematical problem-solving tests, mathematical communication tests, and observation sheets to evaluate student engagement during the learning process. Data analysis was performed using descriptive and inferential statistics to identify significant differences between the experimental group (using PjBL integrated with ethnomathematics) and the control group (using conventional teaching models). The results indicate that the implementation of PjBL integrated with ethnomathematics significantly enhances students' mathematical problem-solving skills and mathematical communication compared to conventional teaching methods. Furthermore, students involved in project-based learning within a local cultural context were better able to relate mathematical concepts to real-life situations, fostering conceptual understanding and creativity. This study concludes that the integration of ethnomathematics in the PjBL model effectively improves the quality of mathematics education in higher education institutions.